1994
DOI: 10.3168/jds.s0022-0302(94)77183-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Additive and Nonadditive Gene Action on Lifetime Yields and Profitability of Dairy Cattle

Abstract: Additive and nonadditive genetic effects on lifetime yields of milk and milk components and lifetime profitability were estimated from 5070 cattle in a Holstein pureline, an Ayrshire-based pureline, and 10 crossbred groups of these purelines. Lifetime yields of milk, fat, protein, and lactose and lifetime milk value and annualized discounted net returns were analyzed. Lifetime yields, lifetime milk value, and annualized discounted net returns of the Holstein x Ayrshire-based line F1 and an F1 x (F1 x F1) cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
3
26
1
1
Order By: Relevance
“…The heterosis effects were favourable for all traits, ranging from 0.1% to 18% of the mean for CR42 in primiparae (mean of 84%) and PRFS (mean of 52%), respectively. Similar conclusions have emerged from controlled experiments (Heins et al, 2008;Begley et al, 2009;Prendiville et al, 2011) and the analysis of national data (McAllister et al, 1994;Wall et al, 2005;Penasa et al, 2010;Coffey et al, 2014). Buckley et al, (2014) documented that heterosis in Holstein-Friesian Jersey crossbreds increases the probability of a cow having a calf born to artificial insemination during the calving period by 3.4%.…”
Section: Breed and Non-additive Genetic Effectssupporting
confidence: 54%
“…The heterosis effects were favourable for all traits, ranging from 0.1% to 18% of the mean for CR42 in primiparae (mean of 84%) and PRFS (mean of 52%), respectively. Similar conclusions have emerged from controlled experiments (Heins et al, 2008;Begley et al, 2009;Prendiville et al, 2011) and the analysis of national data (McAllister et al, 1994;Wall et al, 2005;Penasa et al, 2010;Coffey et al, 2014). Buckley et al, (2014) documented that heterosis in Holstein-Friesian Jersey crossbreds increases the probability of a cow having a calf born to artificial insemination during the calving period by 3.4%.…”
Section: Breed and Non-additive Genetic Effectssupporting
confidence: 54%
“…Earlier studies on experimental herds indicated that crossbreds had superior fertility and longevity compared with Holsteins at the University of Illinois (Touchberry, 1992) and Agriculture Canada (McAllister et al, 1994). Although, until recently, crossbreeding of dairy cattle in North America has been uncommon, it has become a current topic of great interest, developed in response to concerns dairy producers have about fertility, health and survival of lactating Holstein cows (Funk, 2006).…”
Section: Research Findings In the United Statesmentioning
confidence: 99%
“…Thus, the above results for crossbreds should be adjusted downwards, perhaps. Economic heterosis has been estimated at 2-3% [14], and at 16% for lifetime milk yield [5]. The amount of heterosis in this study is indeterminant.…”
Section: Productionmentioning
confidence: 78%
“…Crossbreeding of Holstein dairy cattle to various breeds has been studied in several countries, including Canada, over many years [1][2][3][4][5], but the practice is limited and not exploited as in other species of livestock. Canadian Holstein dams have been mated to sires of other breeds, producing a small population of crossbred animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation